Ancient Mitogenomes Reveal the Evolutionary History and Biogeography of Sloths - Delsuc, Frédéric (2019)
Living sloths represent two distinct lineages of small-sized mammals that independently evolved arboreality from terrestrial ancestors. The six extant species are the survivors of an evolutionary radiation marked by the extinction of large terrestrial forms at the end of the Quaternary. Until now, sloth evolutionary history has mainly been reconstructed from phylogenetic analyses of morphological characters. Here, we used ancient DNA methods to successfully sequence 10 extinct sloth mitogenomes encompassing all major lineages. This includes the iconic continental ground sloths Megatherium, Megalonyx, Mylodon, and Nothrotheriops and the smaller endemic Caribbean sloths Parocnus and Acratocnus. Phylogenetic analyses identify eight distinct lineages grouped in three well-supported clades, whose interrelationships are markedly incongruent with the currently accepted morphological topology. We show that recently extinct Caribbean sloths have a single origin but comprise two highly divergent lineages that are not directly related to living two-fingered sloths, which instead group with Mylodon. Moreover, living three-fingered sloths do not represent the sister group to all other sloths but are nested within a clade of extinct ground sloths including Megatherium, Megalonyx, and Nothrotheriops. Molecular dating also reveals that the eight newly recognized sloth families all originated between 36 and 28 million years ago (mya). The early divergence of recently extinct Caribbean sloths around 35 mya is consistent with the debated GAARlandia hypothesis postulating the existence at that time of a biogeographic connection between northern South America and the Greater Antilles. This new molecular phylogeny has major implications for reinterpreting sloth morphological evolution, biogeography, and diversification history. Extant sloths are the survivors of an evolutionary radiation marked by the extinction of large terrestrial forms of the Ice Age. By sequencing ten mitogenomes from extinct sloths, Delsuc et al. present a new molecular phylogeny revealing widespread morphological convergence with major implications for reinterpreting sloth evolutionary history.